2012
DOI: 10.1074/jbc.m111.334979
|View full text |Cite
|
Sign up to set email alerts
|

Specific Recognition of Biologically Active Amyloid-β Oligomers by a New Surface Plasmon Resonance-based Immunoassay and an in Vivo Assay in Caenorhabditis elegans

Abstract: Background: A␤ oligomers are major players in Alzheimer disease, but the tools for their detection are not satisfactory. Results:We developed a SPR-based immunoassay and a test in C. elegans, specifically identifying toxic oligomers. Conclusion: These methods allow study of the effects of mutations or drugs on A␤ oligomerization. Significance: The SPR-based immunoassay provides new opportunities for the detection of toxic oligomers in biological samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(107 citation statements)
references
References 44 publications
5
99
0
Order By: Relevance
“…22,[36][37][38][39] In particular, our group has demonstrated that Ab 1-42 oligomeric intermediates, but not monomers or fibrils, caused a specific impairment of the worm's pharyngeal function. 21,39 The common pattern of damage exerted by cardiotoxic LCs and Ab oligomers on the worm's pharyngeal cells supports the hypothesis of shared pathways of toxicity between the 2 proteins. One of these, as described later, may involve mitochondria, which are known early targets of damage in Alzheimer disease 40,41 and are particularly abundant in both brain and cardiac muscular cells.…”
Section: Blood 5 June 2014 X Volume 123 Number 23 Amyloid Light-chamentioning
confidence: 55%
See 1 more Smart Citation
“…22,[36][37][38][39] In particular, our group has demonstrated that Ab 1-42 oligomeric intermediates, but not monomers or fibrils, caused a specific impairment of the worm's pharyngeal function. 21,39 The common pattern of damage exerted by cardiotoxic LCs and Ab oligomers on the worm's pharyngeal cells supports the hypothesis of shared pathways of toxicity between the 2 proteins. One of these, as described later, may involve mitochondria, which are known early targets of damage in Alzheimer disease 40,41 and are particularly abundant in both brain and cardiac muscular cells.…”
Section: Blood 5 June 2014 X Volume 123 Number 23 Amyloid Light-chamentioning
confidence: 55%
“…Incubation of the worms with LCs was performed in the absence of E coli to avoid any potential interference between bacteria and the LCs. 14,21 Worms were incubated with 1 to 200 mg/mL BJ or recombinant LCs (100 worms/100 mL) in 10 mM PBS (pH 7.4) or with 50 mg/mL free LCs from patient serum in 5 mM PBS (pH 7.4) (100 worms/100 mL). Control worms were incubated with 10 mM PBS (pH 7.4) (vehicle) only.…”
Section: Elegans Experimentsmentioning
confidence: 99%
“…4G8 recognizes a central region of A␤ (amino acids 17-21, amino acids LVFFA) and a specific signal was evoked by transient oligomers, which were proven to disturb the integrity of artificial lipid bilayers and inhibit the physiological pharyngeal contractions in a Caenorhabditis elegans model. 4G8 bound A␤ oligomers in which the epitope might be exposed in a pseudo-irreversible manner, whereas A␤ monomers where bound with faster dissociation rates [60]. Rushworth at al.…”
Section: Methods For Detection Of Other A␤ Oligomers In Csfmentioning
confidence: 99%
“…[8][9][10][11][12] We recently developed a new approach in which the toxicity of the different protein assemblies can be directly evaluated by administrating them to ancestral worms. 4,13 This is based on the knowledge that the rhythmic contraction and relaxation of the C. elegans pharynx, which is fundamental for the worm's feeding and survival, 14 is sensitive to molecules that can act as "chemical stressors" such as some proteins induced in stress conditions. 15 Using synthetic human suggesting that C. elegans can be used as a "biosensor" for a rapid recognition of the potential toxicity of amyloidogenic proteins.…”
mentioning
confidence: 99%
“…15 Using synthetic human suggesting that C. elegans can be used as a "biosensor" for a rapid recognition of the potential toxicity of amyloidogenic proteins. In addition, the pharyngeal impairment was counteracted by antiamyloidogenic molecules influencing the formation of biologically active oligomers, such as epigallocatechin gallate, 13 indicating that this test can be applied as an inexpensive screening of candidate drugs.…”
mentioning
confidence: 99%